Two Sides of the Same Coin? Integrated vs Standalone Pediatric Psychology Consultation-Liaison (C/L) Service - Amanda Chiapa; Stephanie V. Caldas; David V. Wagner; Becky Lois; Katherine Ort; Rosa Delgado-Kiggins; Rebecca Marshall; Danielle Key; Michael A. Harris (Clinical Practice in Pediatric Psychology, 2026)
In a field where standards of care for subspecialty pediatric psychology services have become increasingly operationalized, the pediatric psychology consultation/liaison (C/L) service can vary substantially as a function of the hospital system in which the service resides. We explore the potential benefits of pediatric psychology C/L services integrated with psychiatry on an inpatient consult service (Integrated) versus existing as a standalone service embedded in pediatrics (Standalone). Data from two similarly sized children’s hospitals in academic medical centers in different regions of the United States were compared (Standalone and Integrated C/L services). Variables included total number of consults seen and nature of consult request for psychology, psychiatry, or both services (psychiatry and psychology). The Standalone C/L service also included data prior to, and following, the onboarding of a fully dedicated psychologist in C/L services. Across both models of C/L, the nature of referrals placed by inpatient medical teams reflected that pediatric psychology C/L provided a specialization separate from psychiatry, as evidenced by different presenting consult concerns. The Standalone C/L service also observed an increase in referrals placed to their service following the onboarding of a full-time psychologist in C/L services. Data suggest that pediatric psychology C/L services are desirable and sustainable regardless of whether they exist as a standalone or integrated model. Implications for Impact Statement The results of the study indicate that pediatric psychology C/L services hold similar value whether they are integrated within inpatient psychiatry C/L services or standalone services in pediatrics.